Testing Brazilians' imports and exports co-integration with monthly data for 1996-2005 - Gilberto Hollauer; Marco Aurélio Alves de Mendonça (Institute for Applied Economic Research (ipea), 2015)
The goal of this paper is to test the Husted model and to inspect the long-run sustainability of Brazilian current account in a very specific period of time (1996-2005) by the use of monthly data. We have tested the inter-temporal budget constraints (IBC) condition via unit root test with structural break and co-integration through Gregory-Hansen test in a 117 long nominal, GDP normalized and CPI normalized series for the Brazilian economy. The results indicated that the pure IBC condition does not hold for the Brazilian economy. However, there is co-integration among the series used in this work and the balance of accounts is sustainable.
Keywords: C12; C22; F21; F43; 330